A comprehensive genetic study reveals a crucial role of CYP90D2/D2 in regulating plant architecture in rice (Oryza sativa). Issue 4 (31st July 2013) - Li, Hui; Jiang, Ling; Youn, Ji‐Hyun; Sun, Wei; Cheng, Zhijun; Jin, Tianyun; Ma, Xiaoding; Guo, Xiuping; Wang, Jiulin; Zhang, Xin; Wu, Fuqing; Wu, Chuanyin; et al.
Summary: Brassinosteroids (BRs) are essential regulators of plant architecture. Understanding how BRs control plant height and leaf angle would facilitate development of new plant type varieties by biotechnology. A number of mutants involved in BR biosynthesis have been isolated but many of them lack detailed genetic analysis. Here, we report the isolation and characterization of a severe dwarf mutant, chromosome segment deleted dwarf 1 ( csdd1 ), which was deficient in BR biosynthesis in rice. We isolated the mutant by screening a tissue culture‐derived population, cloned the gene by mapping, and confirmed its function by complementary and RNAi experiments, combined with physiological and chemical analysis. We showed that the severe dwarf phenotype was caused by a complete deletion of a cytochrome P450 gene, CYP90D2/D2, which was further confirmed in two independent T‐DNA insertion lines in different genetic backgrounds and by RNA interference. Our chemical analysis suggested that CYP90D2/D2 might catalyze C‐3 dehydrogenation step in BR biosynthesis. We have demonstrated that the CYP90D2/D2 gene plays a more important role than previously reported. Allelic mutations of CYP90D2/D2 confer varying degrees of dwarfism and leaf angle, thus providing useful information for molecular breeding in grain crop plants.